History of Islamic Law on Earth Melayu Lancang Kuning Riau-Kepri - Nurhadi Nurhadi (PALAPA, 2019)
Codification and cultural transformation in the Riau Malay region from a local religion to the Islamic religious system, complete with various forms of embodiment of all forms of culture. Revolution and religious reform in Riau Malay society which gave rise to cultural transformation were due to several inherent factors or other factors which were later strongly associated with Islam. Islam when it has to be actualized in culture has presented its face in harmony with the culture of culture in an area, and in the regional diversity of Islamic culture there is still a place for local Islamic culture. However, all cultural diversity is united by spirit and a sacred form of tradition that comes from tawhid. Riau Malay Culture is one of the forms of Islamic culture that has many supporters. Islamic values ​​are clearly seen in various aspects of Riau Malay culture. Malays make Islam the spirit or core of their culture. The history of the entry of Islam, Islamic law, codification and compilation of Islamic law on the yellow Malay land of Riau Kepri tend to be modest, without any resistance mentally, socially, culturally and faithfully. This has led to the Trem that Malays are synonymous with Islam, especially Malay Riau.